Prognostic value of the identified genus of anaerobic bacteria in bloodstream infection beyond host-related risk factors: a five-year retrospective cohort study - Andrea Harmath; Ágnes Jakab; Zoltán Tóth; Aliz Bozó; Bence Balázs; László Majoros; Renátó Kovács (European Journal of Clinical Microbiology & Infectious Diseases, 2026)
Abstract Background Anaerobic bacteraemia is an uncommon but clinically significant bloodstream infection associated with substantial mortality. The respective roles of pathogen-specific and host-related factors in determining outcomes are not fully elucidated. Aim To identify predictors of mortality in anaerobic bacteraemia and to evaluate whether genus-based microbiological classification offers prognostic value beyond established clinical risk factors. Methods A retrospective cohort study was performed involving patients with anaerobic bacteraemia ( n = 96) treated at a tertiary-care centre in Hungary from January 2021 to December 2025. Survival was analysed using Kaplan–Meier estimates and Cox proportional hazards regression. The incremental prognostic value of anaerobic genus was assessed using nested multivariable models, with Firth-penalised logistic regression applied as a sensitivity analysis. Results Among 96 patients (median age 68 years), the most common isolates were Bacteroides spp . (33%), Clostridium spp. (17%), Actinomyces spp . (16%), and Fusobacterium spp. (9%). Mortality rates were 43.8% at 30 days, and 54.2% at 180 days. Survival varied significantly by genus, with Clostridium spp . bacteraemia exhibiting the highest mortality (75.0%). Independent predictors of 180-day mortality were increasing age (HR 1.03, p = 0.037), acute kidney injury (HR 2.27, p = 0.007), liver cirrhosis (HR 2.83, p = 0.022), hypertension (HR 1.95, p = 0.048), and Clost ridium spp. bacteraemia (HR 3.00, p = 0.006). Microbiological classification significantly improved model performance (likelihood-ratio p = 0.016). The final model had an apparent 180-day AUC of 0.81. Conclusions Bacterial genus provides prognostic information beyond host-related risk factors in anaerobic bacteraemia. Clostridium spp. bacteraemia was associated with the highest mortality and independently predicted 180-day mortality.